Immunological properties of a chimeric protein containing the major capsid protein of echovirus 30 (Picornaviridae: Enterovirus: Enterovirus betacoxsackie) - Dmitry A. Melentev; Dmitry V. Novikov; Ekaterina V. Mokhonova; Nadezhda A. Novikova; Alexander Yu. Kashnikov; Svetlana G. Selivanova; Lyudmila N. Golitsyna; Vladislav A. Lapin; Maria I. Tsyganova; Dmitry E. Zaitsev; Viktor V. Novikov (Вопросы вирусологии)
Introduction. Enterovirus infection, widespread in the world and in Russia, is characterized by a variety of clinical forms, one of which is serous meningitis. The most common cause of enterovirus meningitis in children is echovirus 30 (E30). Previously, we obtained a chimeric protein consisting of the S domain of norovirus VP1 protein(SN), fused into one molecule with VP1 protein of E30 (SN-VP1E30), which in the future can be used to develop a vaccine for the prevention of enterovirus meningitis caused by the E30 virus.